2007
DOI: 10.1093/carcin/bgm022
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte polycyclic aromatic hydrocarbon–DNA adduct formation and colorectal adenoma

Abstract: Consumption of charbroiled red meat and meat-derived polycyclic aromatic hydrocarbons (PAHs) has been associated with risk of colorectal adenoma, a precursor of colorectal cancer. Furthermore, leukocyte PAH-DNA adduct levels have been demonstrated to increase in response to charbroiled red meat intake but to date there have been no studies that have investigated the relationship between leukocyte PAH-DNA adduct levels and risk of colorectal adenoma. We investigated the relation of leukocyte PAH-DNA adduct form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 12 publications
2
37
0
4
Order By: Relevance
“…Moreover, as PAHs have the potential to interfere with hormone systems, they can exert harmful effects on reproduction and immune function. As such, DNA damage induced by PAH exposure has been demonstrated by numerous authors (Garcia-Suastegui et al, 2011;Gunter et al, 2007;John et al, 2009). Long-term exposure to PAHs is suspected to raise the risks of cell damage via gene mutation and cardiopulmonary mortality (Kuo et al, 2003).…”
Section: Chronic or Long-term Health Effectsmentioning
confidence: 97%
“…Moreover, as PAHs have the potential to interfere with hormone systems, they can exert harmful effects on reproduction and immune function. As such, DNA damage induced by PAH exposure has been demonstrated by numerous authors (Garcia-Suastegui et al, 2011;Gunter et al, 2007;John et al, 2009). Long-term exposure to PAHs is suspected to raise the risks of cell damage via gene mutation and cardiopulmonary mortality (Kuo et al, 2003).…”
Section: Chronic or Long-term Health Effectsmentioning
confidence: 97%
“…Moreover, as PAHs have the potential to interfere with hormone systems, they can exert harmful effects on reproduction and immune function. As such, DNA damage induced by PAH exposure has been demonstrated by numerous authors (John et al, 2009;Gunter et al, 2007 and Garcia-Suastegui et al, 2011). Long-term exposure to PAHs is suspected to raise the risks of cell damage via gene mutation and cardiopulmonary mortality (Kuo et al, 2003).…”
Section: Acute or Short-term Health Effects:-mentioning
confidence: 92%
“…A recent study by Gunter et al have found that there was a 2.8-fold increase in the risk of colon adenoma in the quartile of individuals with the highest white blood cell PAH DNA adduct levels compared to the lowest quartile [93]. Many other associations have been drawn between adducts and biological effect in human studies, which have been well summarised in the review of Kyrtopoulos [94].…”
Section: Validation Of Dna Adduct Determination and Its Use In Risk Amentioning
confidence: 99%